Kosher and Halal Business Compliance - Lever, John; Fischer, Johan; Taylor and Francis (Boca Raton, FL : Routledge, an imprint of Taylor and Francis, 2018)
Kosher is a Hebrew term meaning 'fit' or 'proper' and halal is an Arabic word that literally means 'permissible' or 'lawful'. Within the last two decades or so, kosher and halal markets have become global in scope and states, manufacturers, restaurants, shops, certifiers and consumers around the world are faced with ever stricter and more complex requirements - most clearly exemplified by Muslim and Jewish groups' call for kosher and halal certification by third party certification bodies. During this period hundreds of kosher and halal certifiers have emerged around the world, and while thousands of manufacturers, restaurants and shops have been certified, the majority have not. Kosher and halal requirements are comparable, but there are also many differences and the book discusses how these similarities and differences affect production, trade and regulation around the world. The authors research demonstrates that there is a need to address kosher and halal markets simultaneously and answers the question "what characterizes global kosher and halal markets and how can businesses comply with the rising demands and requirements that have emerged?"This is the only book of its kind and it will appeal to manufacturing companies, restaurants and shops that already are or want to be kosher/halal certified. The book can also be assigned in a variety of upper-level undergraduate courses and graduate seminars in business studies, management and marketing. Moreover, the book will be of interest to readers in the natural sciences (for example, food scientists) and outside academia, that is, to state as well as non-state kosher/halal certification bodies, policy makers, interest groups and consultants. Kosher and Halal Business Compliance is accessible in style, global in scope and based on decades of research.
Jewish and Arabic Terms --, Part one, --1. -- Introduction, 2. What is kosher and halal? 3. Similarities and differences between kosher and halal, --Part two, --4. Certification, inspections and logos, 5. Standards, 6. Kosher and halal certification, 7. Government, 8. Consumers, --Part three, --9. -- Meat and poultry production, 10. Biotech production, 11. Dairy, 12. Bread and Bakery, 13. Fruit and Vegetables, 14. Shops, 1. Restaurants, 16. The food service industry and public institutions, 17. Training, 18. Science, 19. Conclusions, -- Index.
Includes bibliographical references and index.
Also available in print format.
Keywords: BUSINESS & ECONOMICS / Industries / Food Industry; SOCIAL SCIENCE / Islamic Studies; Food industry and trade -- Handbooks, manuals, etc; Kosher food industry -- Handbooks, manuals, etc; Halal food industry -- Handbooks, manuals, etc; Food adulteration and inspection -- Handbooks, manuals, etc; Food law and legislation -- Handbooks, manuals, etc; Food adulteration and inspection; Food law and legislation; Halal food industry; Kosher food industry; Electronic books